Volumetric analysis and chemistry students performance: Combined influence of study habit, physiological and psychological factors - Alam, G.M.; Oke, O.K.; Orimogunje, T. (Academic Journals, 2010)
Several factors can work in concert to influence the students' attitudes and behavior towards quantitative aspect of practical chemistry particularly volumetric analysis. This study investigated the influence of students' study habit, physiological and psychological factors on their attitudes and behavior towards the volumetric analysis in practical chemistry. Two hundred and forty randomly selected senior secondary two students from six secondary schools in Akure South Local Government Area of Ondo State constituted the sample. It was hypothesized that students' study habit variables such as time allocation, reading and note-taking, concentration, anxiety and stress, and teachers' consultation would not significantly influence students' attitudes during volumetric analysis practical exercises. The hypotheses were tested by using chi square at 0.05 levels of significance following the administration of study habit inventory on the subjects. The results indicated that these factors actually influenced the attitudes of the subjects towards volumetric analysis exercises. It was recommended that chemistry teachers need to have proper understanding of these physiological and psychological factors to enable them enhance students' attitudes and performances in practical chemistry.